Nomogram of corpus callosum length and thickness in turkish population (Annals of Medical Research, 2022)
Objectives: Central nervous system (CNS) malformations constitute an important part of congenital anomalies and corpus callosum anomalies are highly associated with other CNS abnormalities. Starting from this point of view we conducted a retrospective study providing reliable reference charts for accurate fetal corpus callosum measurements.Materials and Methods: The corpus callosum length (CCL) and thickness (CCT) were measured in the midsagittal plane. The CCL was measured from the most anterior part of the genu to the most posterior part of the splenium (outer-outer),  the thickness of the body was measured as well.Results: Study included 1152 patients. 95.6% of the detailed ultrasonographies were performed between 19-21 gestational weeks and 611(63.0%) were performed at 20th gestational week. The mean values of the CCL and CCT measurements were from 16.9 mm to 25.5 mm and from 1.3 mm to 2.0 mm, respectively with increasing gestational weeks. Third percentile for CCL was 14.6 mm, 16.2 mm and 17.9 mm for 19th, 20th and 21th gestational weeks, respectively and median CCL values were 17.7mm, 19.5mm and 21.7mm for 19th, 20th and 21th gestational weeks respectively.Conclusion: Our study demonstrates that defining and using corpus callosum length and thickness charts characteristic for our population may improve diagnostic accuracy of corpus callosum presence and structure. Objective measurements of CC may help to identify developmental anomalies of CNS and enable better prenatal counseling.
Keywords: Central nervous system; Congenital Abnormalities; Corpus Callosum; Corpus Callosum Agenesis; Fetal Abnormalities.